Effects of management strategies on animal welfare and productivity under heat stress: A synthesis - Morgado, Joana Nazaré; Lamonaca, Emilia; Santeramo, Fabio Gaetano; Caroprese, Mariangela; Albenzio, Marzia; Ciliberti, Maria Giovanna (Frontiers in Veterinary Science, 2023)
Climate change includes different dramatic events, and among them, heat stress exposition is the strongest phenomenon affecting the livestock sector. The effects of heat stress events on animal welfare are complex and the economic impacts for the livestock sector are relevant. Management measures may contribute to improve the resilience to heat stress, but the extent to which they impact on livestock performances and management strategies depend on the magnitude of the stress conditions. Through a pioneering synthesis of existing knowledge from experiments conducted in controlled conditions, we show that management strategies, both adaptation and mitigation measures, halved the negative impacts on the ruminants’ performances and welfare induced by heat stress, but the efficacy is low in extreme conditions, which in turn are more and more frequent. These novel findings emphasise the need to deepen research on more effective adaptation and mitigation measures.